2017
DOI: 10.1039/c7nj00878c
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical elucidation: why does a SO3H-functionalized imidazolium-based ionic liquid catalyze the conversion of 5-hydroxymethylfurfural to levulinic acid?

Abstract: DFT calculations show a clear picture of how a SO3H-functionalized imidazolium-based ionic liquid catalyzes the conversion of 5-HMF to LA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Simultaneously, the by-product LA yields were significantly decreased to 2.9%, 3.9% and 2.1%, respectively. These results suggest that adding a small amount of imidazole ionic liquids with halogen anions was favorable for more selective HMF formationin [Bmim]HSO4 can further facilitate the rehydration of HMF to produce LA 59,60. All the above results indicate that dialkylimidazole-based ionic liquids with halogen anions could effectively improve the selectivity and yield towards HMF in water media while the others (e.g., [Bmim]BF4, [Bmim]PF6 and [Bmim]HSO4) exhibited the negative effect.…”
mentioning
confidence: 96%
“…Simultaneously, the by-product LA yields were significantly decreased to 2.9%, 3.9% and 2.1%, respectively. These results suggest that adding a small amount of imidazole ionic liquids with halogen anions was favorable for more selective HMF formationin [Bmim]HSO4 can further facilitate the rehydration of HMF to produce LA 59,60. All the above results indicate that dialkylimidazole-based ionic liquids with halogen anions could effectively improve the selectivity and yield towards HMF in water media while the others (e.g., [Bmim]BF4, [Bmim]PF6 and [Bmim]HSO4) exhibited the negative effect.…”
mentioning
confidence: 96%
“…Li et al. also found this to be the case when they modeled the rehydration of HMF in the presence of an ionic liquid catalyst, where the more energetically favorable pathway to levulinic acid was found to go via 8 (non‐deuterated) . Yang and co‐workers came to the same general conclusion, where levulinic acid was proposed to result from the hydrolysis of an angelica lactone intermediate .…”
Section: Methodsmentioning
confidence: 99%
“…Our previous mechanistic studies on BILscatalyzed dehydration and cyclization of lignocellulose-derived compounds showed that the cooperation of cations and anions of BILs can lead to unexpected mechanistic profiles. [18,19] Inspired by this, we attempt to do a systematic study on the mechanism using density functional theory (DFT), from which we expect reveal (i) what the roles of the cation and anion of BIL are, (ii) the reasons for discrepancies of reaction rates and association equilibrium constants, (iii) the essential cause of the structure-sensitive catalytic activities of BILs toward sorbitol dehydration. The calculated results are expected to provide important insights into the reactions and to explain the experimental observations.…”
Section: Introductionmentioning
confidence: 99%
“…have performed a computational study on the mechanism of cellulose hydrolysis, which is the reverse reaction of dehydration, and proposed a S N 2‐type‐like mechanism. Our previous mechanistic studies on BILs‐catalyzed dehydration and cyclization of lignocellulose‐derived compounds showed that the cooperation of cations and anions of BILs can lead to unexpected mechanistic profiles [18,19] . Inspired by this, we attempt to do a systematic study on the mechanism using density functional theory (DFT), from which we expect reveal (i) what the roles of the cation and anion of BIL are, (ii) the reasons for discrepancies of reaction rates and association equilibrium constants, (iii) the essential cause of the structure‐sensitive catalytic activities of BILs toward sorbitol dehydration.…”
Section: Introductionmentioning
confidence: 99%